A Note on Asymmetric Thick Branes. (11th June 2014) - Bazeia, D.; Menezes, R.; da Rocha, R.
Abstract : We study asymmetric thick braneworld scenarios, generated after adding a constant to the superpotential associated with the scalar field. We study in particular models with odd and even polynomial superpotentials, and we show that asymmetric brane can be generated irrespective of the potential being symmetric or asymmetric. We study in addition the nonpolynomial sine-Gordon like model, also constructed with the inclusion of a constant in the standard superpotential, and we investigate gravitational stability of the asymmetric brane. The results suggest robustness of the new braneworld scenarios and add further possibilities of the construction of asymmetric branes.